Management strategies for St. Mark Learning Center - Tan, Lalaine T. (Animo Repository, 1997)
Background St. Mark Learning Center was established by Mrs. Lilian Tan Siy in fulfillment of her dream to set-up a pre-school catering to pre-schoolers and special children. The directress established the pre-school to answer to the community's need for a high standard learning venue as it had become a requirement for entrance in the Nursery of Kindergarten level. There has been a noticeable increase in the number of pre-schools in the Metro Manila in the past few years, and as more pre-schools open up, existing pre-schools are now faced with the challenge to cope with changing needs of the industry as well as its clients. As the Department of Education, Culture and Sports has encouraged the establishment of additional institutions to provide easier access to education, competition continues to intensify. On its 12th year of operation, the management of the staff would like to continue its commitment to provide learning experiences for the total development of the child through sensorial education, practical life and independence training, the inculcation of the basic Christian values and assistance in the acquisition of socially acceptable behaviors for satisfying social participation in the home, school and community. St. Mark Learning Center aims to provide quality education and preparation for the children and to assist parents in the value formation of their children.